Sword and the Lotus - OSHO ("Cologne, Germany")
This volume captures the fast pace of Osho's six-week stay in Nepal, the birthplace of Buddha. He answers questions from his sannyasins in his hotel suite in the mornings, from representatives of the press every evening in the hotel conference room: What is your message to the modern Nepalese Buddhists? What is your message for the Pope who is in India now? What do you think about the New Age movement? You teach us to be thankful to existence, but how can I be thankful to those who speak against you and try to destroy your work? With no white lies, no beating around the bush, no platitudes and no mincing of words, Osho's truth cuts clean with the skill of a master swordsman, and with the compassion symbolized in the lotus.
Keywords: Meditation